Early metastasis to anterior abdominal wall following radical cystectomy: A rare presentation - Ajit Sawant; Sumit Bansal; Prakash Pawar; Gaurav Kasat (Urology Annals, 2016)
Abdominal wall metastasis from urothelial cancer is extremely rare and very few such cases have been reported in the literature. As such the treatment protocols are not so well defined. We present an interesting case of a 65-year-old male patient, known case of chronic kidney disease, who presented with a large, fungating infraumbilical mass 8 months postradical cystectomy. The mass involved full thickness anterior abdominal wall and small bowel including the ileal conduit. Wide excision of the mass along with adhered bowel loops and partial excision of the ileal conduit with right ureteric reimplant was performed. The large defect in the anterior abdominal wall was closed using a mesh (permanent with a bioresorbable coating inside) and myocutaneous thigh flap. The histopathological examination of the excised mass was consistent with secondary from the urothelial tumor.